Divine complexity : the rise of creedal Christianity - Hinlicky, Paul R. (Minneapolis, Minn. : Fortress Press, 2011)
"Paul Hinlicky reads the history of the early church as a genuine, centuriesilong theological struggle to make sense of the confession of Jesus' life, death, and resurrection. Protesting a recent parting of the ways between systematic theology and the history of early Christianity, Hinlicky relies on the insights of historical criticism to argue in this historical survey for the coherence of doctrinal development in the early church. Hinlicky contends that the Christian tradition shows evidence of being governed by a hermeneutic of 'cross and resurrection.' In successive chapters he finds in the New Testament writings a collective Christological decision against docetism; in the union of Old and New Testaments, a monotheistic decision against Gnostic dualism; in the resulting sweep of the canon a narrative of the divine economy of salvation that posed a trinitarian alternative to Arian Unitarianism; and in the insistence upon the cross of the incarnate Son, a rebuke of Nestorianism" -- Publisher description.
The primacy of the gospel -- From resurrection kerygma to gospel narrative -- The scriptures' emergence as the church's canon -- The trinitarian rule of faith -- The confrontation of biblical and philosophical monotheism -- The holy Trinity as the eternal life -- Postscript: The "impassible passibility" of the Trinity.
Includes bibliographical references (p. 241-275) and index.
Keywords: Bible. -- Theology; Trinity -- History of doctrines